Comparative Behavior of Foreign and Domestic Export Firms in a Developing Economy - Cohen, Benjamin I. (The Review of Economics and Statistics, 1973)
D ESPITE failure of rich countries to grant any new tariff preferences to less developed countries (LDC's) 1960's, export earnings of manufactures by LDC's grew by more than 10 per cent per year during decade.' This phenomenon seems related to !the expansion of multinational firm. Scattered bits of evidence suggest that a large fraction of exports of manufactures from LDC's are accounted for by such firms. Between 1965 and 1968 annual exports from LDC's by foreign affiliates of United States manufacturing firms rose from 700 million dollars to 1.4 billion dollars.2 Between 1957 and 1966 Latin America's annual exports of manufactures rose from 709 million dollars to 1,613 million dollars, and subsidiaries of United States firms accounted for 65 per cent of this increase of 804 million dollars.3 IBM is said to have been largest single exporter of manufactures from both Argentina and Brazil 1969.4 As is well known, there is a large amount of literature on question of impact on currently less developed countries of large increase their exports of primary products during 19th century. We do not have much evidence on impact of contemporary investment by foreign manufacturing firms LDC's.5 The Pearson Commission (1969, p. 104) said in absence of detailed empirical studies, it is difficult to pass a definitive verdict on precise size of contribution which foreign investment has made to development. 6 Vernon (1971, p. 181), discussing extent to which foreign firms introduce into developing countries production techniques that are excessively capital intensive, says the actual facts are, as usual, obscure. There are no comprehensive data on degree to which multinational enterprises adapt their production processes to conditions of less-developed countries, and scarcely any data on comparative adaptive actions of local competitors. The next two sections present data on a sample of Japanese and United States firms South Korea, and final section discusses benefits and costs to South Korea of these foreign investments.